Potential Health Impacts from Radioactive Releases at Rooppur Nuclear Power Plant Under Hypothetical Accident Scenario (MIST International Journal of Science and Technology, 2025)
This study presents a comprehensive assessment of radiological dose consequences from potential severe accident scenarios at the Rooppur Nuclear Power Plant (NPP), focusing on health impacts from radioactive releases. Utilizing HotSpot 3.1.2 and ORIGEN 2.2, the research estimates Total Effective Dose Equivalent (TEDE) and Committed Effective Dose Equivalent (CEDE) to critical organs, including the thyroid, skin, lungs, surface bone, red marrow, and liver, under seasonal meteorological conditions. The thyroid, due to its high affinity for radioactive iodine (particularly 131I), showed maximum CEDE values of 8.0 × 105 Sv and 4.4 × 105 Sv during the autumn and rainy seasons, respectively, at 30 meters from the source. These values, along with other organ doses, exceeded public and occupational dose limits up to 15 km in the rainy season and 30 km in the autumn season, primarily influenced by wind speed and precipitation. The study underscores the need for emergency protective measures such as sheltering, evacuation, and the administration of potassium iodide (KI), especially for populations within high-risk zones. It further recommends the integration of dose modeling findings into the National Nuclear and Radiological Emergency Preparedness and Response Plan (NNREPRP) to enhance response strategies and protect public health in the event of nuclear accidents.MIJST, V. 13,December 2025: 15-25https://doi.org/10.47981/j.mijst.13(02)2025.524 (15-25)